CSR dan Pendanaan LSM di Yogyakarta - Nanda, Dendy H (Universitas Brawijaya, 2020)
This article aimed to describe how CSR funds play in the funding of NGOs in Indonesia. The flow of CSR funds from foreign companies to NGO engaged in the community is certainly raised the questions, seeing the very different spirit between corporate NGO. The corporation whose orientation is on financial gain, while the orientation of NGO is community empowerment and it is a non-profit institution. Therefore, we need to pay attention to the power-corporate relations in the NGO through the funding network. This research uses qualitative methods based on a critical paradigm. It was found that the Corporate Social Responsibility (CSR) is no longer merely an act of charity and the social kindnes of the company to its community, furthermore, it is already a business strategy. The knowledge and power of funds agencies has been